O ensino de sociologia nos itinerários formativos das escolas de ensino médio em tempo integral no Ceará - Gomes, Daniela Bezerra de Menezes (2024)
The present research work analyzes how Sociology manifests itself in the composition of the formative itineraries offered in the final stage of Basic Education within the context of the New High School in Secondary Education in Full-Time High Schools (EEMTI) in the state of Ceará. More specifically, it investigates how the theories, concepts and themes of Sociology are expressed in the Elective Curricular Unit (UCE) entitled Sociology for Enem. As a contribution, this work also provides a booklet aimed at mitigating the absence of structured teaching material and supporting teaching practice, mobilizing sociological concepts and teaching resources that integrate the field of sociological knowledge with other areas of knowledge. Considering the agents directly involved in the Brazilian curriculum organization, through the High School Reform, the research was conducted based on a theoretical framework that exposes the fronts of action and the position of the corresponding agencies and agents in the private and/or private sectors representing international financial organizations in the process of reconfiguring the curricular architecture of state departments. As a result, the research presents the objectives and scope of Brazilian public educational policies in the context of the New High School, considering the challenges imposed by the reorganization of curricula to meet global logic and the possibilities that may arise as a perspective for the human emancipation of students. The methodology applied in this work is characterized as qualitative, through the application of an online or face-to-face questionnaire with teachers who taught the UCE - Sociology for Enem, in the year 2022, in the state education network of the state of Ceará. Based on the reports of the surveyed teachers, it can be observed that the proposal to work with the UCE - Sociology for Enem goes beyond the concept of restricted and unilateral teaching, disseminated by the Secondary Education Reform which, in general terms, promotes and defends the idea of teaching with an emphasis on the world of work and the hegemony and hierarchization of subjects due to the overvaluation of Mathematics and Portuguese, including applying this interpretation to the diverse part of the curriculum. In practice, UCE - Sociology for Enem proposes to act in the political-citizen training of young people and in defense of an education that seeks the human emancipation of students. Finally, the research aims to alleviate the relative skepticism that scares Sociology about the impossibility of reversing the condition of hierarchization of knowledge, highlighting the possibilities of mobilizing training itineraries with a view to strengthening the pedagogical identity of the discipline and the teacher.